Multifunctional Spun Yarns and Textiles from Nickel‐Titanium Microfilaments. Issue 6 (8th April 2020) - Weinberg, Charles A.; Cai, Song; Schaffer, Jeremy; Abel, Julianna
Abstract: Improvements in multifunctional materials have led researchers to reinvigorate traditional textile structures by integrating emerging material technologies to offer novel solutions to diverse industries. However, there exist few multifunctional materials capable of being produced with micrometer diameters that can be spun into yarns for textile manufacturing, limiting the wearability and tunability of multifunctional textiles. Here, the creation of nickel‐titanium (NiTi) smart material‐based yarns is enabled by the availability of small diameter (≤10 µm) NiTi filaments that can survive the yarn spinning manufacturing process. NiTi microfilament yarns exhibit traditional superelastic and shape memory properties, and afford additional improvements to mechanical performance such as a tunable structural stiffness, plateau strength, and actuation contractions through the introduction of controllable geometric parameters—yarn count, surface twist angle, and manufacturing strains. This work concludes in a densely knitted, closed‐form textile with shape memory actuation and superelastic recovery. NiTi microfilament yarns and textiles have promising impacts in actuating and energy‐absorbing technologies for medical, robotics, aerospace, and defense applications. Abstract : Here, NiTi‐based micrometer‐sized shape memory alloy filaments are developed, and their integration into yarn structures, improving the tailorability of NiTi mechanical performance, is demonstrated. This research has promising impacts in actuating and energy‐absorbing technologies for medical, robotics, aerospace, and defense applications by creating the first cloth‐like knitted textile to exhibit both the superelastic and shape memory effects.